(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Today both state and central governmentshould focus on entrepreneurial education so that the performance ofentrepreneurs is enhanced and which leads to industrial development andultimately economic growth of the country can be enhanced. Technologydevelopment should be emphasizing in the light of global competition. Financialinfrastructure need to be broadened and adequate inflow of credit to the sectorbe ensured taking into consideration the growing investment demand. Aboveproblems are generated from lack of entrepreneurial education. If educationsector is restructured and entrepreneurship subject is given importance thenMadhya Pradesh would be best industrial area of the country.